The Use of a Personal Computer in the Pulmonary Function Tests of Laboratory Rats - Massad, E.; Furuie, S. Sh.; de Assis Moura, L., Jr.; Nascimento Saldiva, P. H.; Nicolelis, M. A.; Böhm, G. M. (Methods of Information in Medicine, 1985)
A system consisting of an 8-bit word microcomputer of the APPLE line equipped with an analog-to-digital converter, connected to a physiograph measuring pressures from a whole-body Plethysmograph, was used to perform pulmonary tests in rats. The system proved to be time-saving without loss in accuracy when compared to manual calculation methods. It allows measurement repetition during the same experiment, which is impossible by manual techniques, and permits to obtain flow/volume relationships without pneumotachographs or integrator and/or differentiator modules. This approach may be applied to humans and used by any physician.
Keywords: Pulmonary Function; Personal Computer; Physiology; Digital-to-Analog Converter; Biological Signal Processing